Extensive localization of long noncoding RNAs to the cytosol and mono- and polyribosomal complexes - van Heesch, Sebastiaan; van Iterson, Maarten; Jacobi, Jetse; Boymans, Sander; Essers, Paul B; de Bruijn, Ewart; Hao, Wensi; MacInnes, Alyson W; Cuppen, Edwin; Simonis, Marieke (Genome biology, 2014)
BACKGROUND: Long noncoding RNAs (lncRNAs) form an abundant class of transcripts, but the function of the majority of them remains elusive. While it has been shown that some lncRNAs are bound by ribosomes, it has also been convincingly demonstrated that these transcripts do not code for proteins. To obtain a comprehensive understanding of the extent to which lncRNAs bind ribosomes, we performed systematic RNA sequencing on ribosome-associated RNA pools obtained through ribosomal fractionation and compared the RNA content with nuclear and (non-ribosome bound) cytosolic RNA pools. RESULTS: The RNA composition of the subcellular fractions differs significantly from each other, but lncRNAs are found in all locations. A subset of specific lncRNAs is enriched in the nucleus but surprisingly the majority is enriched in the cytosol and in ribosomal fractions. The ribosomal enriched lncRNAs include H19 and TUG1. CONCLUSIONS: Most studies on lncRNAs have focused on the regulatory function of these transcripts in the nucleus. We demonstrate that only a minority of all lncRNAs are nuclear enriched. Our findings suggest that many lncRNAs may have a function in cytoplasmic processes, and in particular in ribosome complexes.